ANALISIS PERILAKU KONSUMEN PADA PRODUK KOSMETIK HALAL - Fitriani, Dyah (Jurnal Fokus Manajemen Bisnis, 2012)
Current research aimed to investigate the effects of consumer perception and product attribute, both simultaneously and partially, on consumer behavior of halal products. This research involved respondents namely female students of management department, Faculty of Economics, Ahmad Dahlan University (the students used both decorative and threatment cosmetics). Researcher used simple random sampling, and the tools used in the current research was mutiple regression analysis, F test, t test, and chi-square test. The result showed that there were no significant effect of consumer perception and product attribute simultaneously on consumer behavior of halal products.